Stock Transaction Manipulation - Rahima Br Purba; Junawan (Yayasan Multidimensi Kreatif, 2025)
The Indonesian capital market continues to grow rapidly with the increasing number of retail investors in recent years. However, this growth is also accompanied by the phenomenon of stock transaction manipulation, especially in small-cap stocks or known as